Recurrence rate of hepatocellular carcinoma in patients with treated hepatocellular carcinoma and hepatitis C virus‐associated cirrhosis after ombitasvir/paritaprevir/ritonavir+dasabuvir+ribavirin therapy. Issue 5 (1st June 2019) - Preda, Carmen M; Baicus, Cristian; Sandra, Irina; Oproiu, Alexandru; Manuc, Teodora; Constantinescu, Ileana; Gavrila, Daniel; Diculescu, Mircea; Dumitru, Radu; Vasilescu, Catalin; Tieranu, Cristian; Istratescu, Doina; et al.
Abstract : Introduction: Recent studies have suggested a higher recurrence rate of hepatocellular carcinoma (HCC) in patients with a history of HCC and hepatitis C virus (HCV)‐associated cirrhosis treated with direct‐acting antiviral (DAA) agents. Material and methods: We conducted a prospective analysis of 24 patients with HCV‐associated cirrhosis and treated HCC who received ombitasvir/paritaprevir/ritonavir+dasabuvir+ribavirin for 12 weeks. Prior therapies for HCC included resection (9/24 patients), radiofrequency ablation (RFA) (7/24) and trans‐arterial chemoembolization (TACE) (8/24). All patients were eligible for treatment if they had no HCC recurrence 6 months after their last procedure. A control group was defined. All patients were followed every 6 months, with dynamic computed tomography and/or magnetic resonance imaging. Results: The sustained virological response rate per protocol was 21/24 (87.5%). The study group included 14 (59%) males, median age 64 years (51–77), 50% with associated non‐alcoholic steatohepatitis and 24% with Child–Pugh A6 points. HCC recurrence rate/100 patient‐years was lower in the DAA‐HCC group versus control: 5.5 versus 24.6% patient‐years for the resection+RFA group ( p  = 0.044), respectively, and 18.6 versus 72.7% patient‐years for TACE group ( p  = 0.002). Survival without recurrence was higher in the resection+RFA group (45 compared to 18 months ( p  < 0.001)) and also in the TACE group (44 compared to 11.5 months ( p  = 0.002)). Conclusions: DAA therapy significantly reduced the recurrence rate of HCC and improved survival without recurrence in patients with treated HCV‐associated HCC.